The Role of Nurses and Community Health Workers in Confronting Neglected Tropical Diseases in Sub-Saharan Africa: A Systematic Review. - Andrew G Corley; Clifton P Thornton; Nancy E Glass (PLoS Neglected Tropical Diseases, 2016)
INTRODUCTION:Neglected tropical diseases produce an enormous burden on many of the poorest and most disenfranchised populations in sub-Saharan Africa. Similar to other developing areas throughout the world, this region's dearth of skilled health providers renders Western-style primary care efforts to address such diseases unrealistic. Consequently, many countries rely on their corps of nurses and community health workers to engage with underserved and hard-to-reach populations in order provide interventions against these maladies. This article attempts to cull together recent literature on the impact that nurses and community health workers have had on neglected tropical diseases. METHODS:A review of the literature was conducted to assess the role nurses and community health workers play in the primary, secondary, and tertiary prevention of neglected tropical diseases in sub-Saharan Africa. Articles published between January 2005 and December 2015 were reviewed in order to capture the full scope of nurses' and community health workers' responsibilities for neglected tropical disease control within their respective countries' health systems. RESULTS:A total of 59 articles were identified that fit all inclusion criteria. CONCLUSIONS:Successful disease control requires deep and meaningful engagement with local communities. Expanding the role of nurses and community health workers will be required if sub-Saharan African countries are to meet neglected tropical disease treatment goals and eliminate the possibility future disease transmission. Horizontal or multidisease control programs can create complimentary interactions between their different control activities as well as reduce costs through improved program efficiencies-benefits that vertical programs are not able to attain.